The Correlation between Parents' Digital Literacy Knowledge and Parents' Perception of Digital Literacy Knowledge of Elementary School Students - Yelsa Harafani Mulya; Zetra Hainul Putra; Neni Hermita (STAI Hubbulwathan Duri, 2023)
This research aimed to examine the relationship between parents’ digital literacy knowledge and parents’ perceptions of elementary school students’ digital literacy knowledge. The data collection method in this study was by distributing questionnaires through instruments tested for validity. Digital literacy in this study was based on four indicators: information, communication, content creation, and safety. Meanwhile, to measure perception based on three indicators: attention, experience, and knowledge. The sampling technique used was saturated sampling, namely, 80 respondents namely consisting of parents of fourth-grade elementary school students. This study used quantitative correlational methods with data analysis used in hypothesis testing, namely the product-moment correlation test. The results of this study with a significance value of 1,319 1,66 indicated no significant relationship between parents’ digital literacy knowledge and parents’ perceptions of elementary school students’ digital literacy knowledge. The correlation coefficient value was 0,148, which results were included in the fragile category (not correlated) in the correlation test; Ha was rejected, Ho was accepted, and it could be concluded that there was a positive but not significant relationship. So the results obtained after conducting this research were that there was no significant correlation between parents’ digital literacy knowledge and parents’ perceptions of the digital literacy knowledge of elementary school students knowledge.